The jaguar Panthera onca (Carnivora: Felidae) in “El Cielo” Biosphere Reserve, Tamaulipas, Mexico - Carrera-Treviño, Rogelio; Lira-Torres, Ivan; Martínez-García, Luis; López-Hernández, Martha (Revista de Biología Tropical, 2016)
Information on the ecology of jaguars (Panthera onca) in “El Cielo” Biosphere Reserve in Tamaulipas, Mexico is scant and limited to anecdotic records in a handful of publications. The objectives of our study were to: a) determine population density and structure of jaguars, b) compare their activity patterns with that of pumas (Puma concolor), c) ascertain potential prey relative abundance, and d) evaluate local resident’s perception on loss of domestic animals due to jaguar predation. Between April 2013 and April 2014 we conducted camera trapping in Gomez Farias Township with a total sampling effort of 8 580 camera trap days. Besides, we completed 136 semi-structured interviews among local residents of Gomez Farias and Llera Townships to gather information on domestic animal losses attributed to jaguars and other carnivores. We identified eight different jaguar individuals during a complete year of camera-trapping, composed of four adult females, one juvenile female, two adult males and one juvenile male. We estimated a jaguar density of 5.9 ± 1.3 jaguars/100 km². Activity patterns for jaguars and pumas were similar as both were nocturnal and crepuscular in nature. The most abundant potential prey species for jaguars in the study site were Crax rubra, Cuniculus paca, Mazama temama, Odocoileus virginianus and Didelphis virginiana; while the rarest were Mephitis macroura and Procyon lotor. Interview results suggested that chickens, dogs, and house cats were the most consumed domestic animals from all reported losses by local residents (n= 107). This study represents the first attempt to describe jaguar ecology in “El Cielo” Biosphere Reserve; however, there is a need of additional monitoring efforts to determine the current status of jaguars in a larger area in order to establish conservation strategies. Finally, this jaguar population may have an important role in maintaining the species in the Sierra Madre Oriental biological corridor connecting populations in Nuevo Leon and San Luis states in Northeastern Mexico.